Optoelectronic Fibers: Single‐Crystal Germanium Core Optoelectronic Fibers (Advanced Optical Materials 1/2017). Issue 1 (January 2017) - Ji, Xiaoyu; Page, Ryan L.; Chaudhuri, Subhasis; Liu, Wenjun; Yu, Shih‐Ying; Mohney, Suzanne E.; Badding, John V.; Gopalan, Venkatraman
Abstract : The image depicts laser‐induced crystallization of the amorphous germanium core of a silica optical fiber in order to create a long and perfect single crystal of germanium inside the fiber. In article number 1600592, J. V. Badding, V. Gopalan, and co‐workers demonstrate that such single crystal fibers with low optical propagation loss, high photosensitivity in the infrared, and nearly intrinsic optoelectronic properties as bulk germanium single crystal could be a building block for the vision of allfiber optoelectronics, where light generation, modulation, and detection can occur within the optical fiber network.